Nanoindentation studies of polyimide thin films on silicon substrates - Yeo, Elaine (2014)
With the advancements in microelectronic industry and extensive use of thin films in the micro-devices, there has been an increasing interest in characterising their mechanical properties especially since they could be different from the identical bulk material. Nanoindentation has become a widely used method due to its ability to probe in the submicron scale and its simplicity in obtaining mechanical properties for films adherent on substrate under essentially compressive conditions. It is a continuous depth and load sensing system which gives load-displacement data that are analysed to give the hardness and modulus of the films. It has been proven useful for testing many metals and ceramics and it is of interest to use it for polymeric materials too. Polyimide is a material commonly used in microelectronics and in thin film forms. Thus, it would be of interest to probe the mechanical properties of this polyimide thin film with nanoindentation technique. There are however, additional challenges in obtaining reasonable properties from this technique for polymeric materials. In this project, the hardness and modulus values of PMDA-ODA polyimide thin films in the thickness range of 1 to 50 μm were studied using existing nanoindentation methods and analysis procedures. Depth independent modulus obtained is 5.3 ± 0.3 GPa and steady state hardness is 0.25 ± 0.02 GPa. The modulus measured is higher than the 2.5 - 3 GPa obtained for other tests including uniaxial tensile and bulge tests. The various factors affecting the measurement and uncertainties involved were discussed. The more prominent ones are the substrate effect, contact area determination, indentation creep behaviour and thermal drift effect. There is also an attempt to address the time-dependent behaviour of this polymeric material using nanoindentation constant load hold technique.